enter image description here

I am able to do all the parts except the very last. I have been trying to coax the differential equation $\frac{M'}{M}=t$ or something to that effect but I don't see how I can achieve this. Hints would be much appreciated.


We have $M(2t)=M(t)^3 M(-t)$ and $M(t)=M(-t)$, so $M(2t)=M(t)^4$. Hence we have a functional equation for $m(t)=t^{-2}\log M(t)$ (let $m(0)=\frac12s^2=\frac12$): $$m(2t)=m(t)\quad\text{for all }t\tag{1}$$ But we know $$ m(t)=\frac12+o(1)\text{ for small }t\tag{2} $$ from the expansion of $M(t)$.

Now equations (1) and (2) together implies $m$ is constant $\frac12$. Can you see why?

  • $\begingroup$ So letting $o(1) = f_1(t)$ we can see that $f_1(t)=f_1(2t) \implies f$ constant and $m(0) = 1/2$ gives the result? Question: how did we get equation (2) $\endgroup$ – user3184807 May 22 at 10:13
  • 1
    $\begingroup$ Not quite. By (1), $m(t)=m(t/2)=m(t/4)=\dots$. By (2), we have $m(t/2^n)\to\frac12$. The only way to reconcile these two is if $m(t)=\frac12$, any other value would violate the limit. $\endgroup$ – user10354138 May 22 at 10:16
  • $\begingroup$ oh yes of course $\endgroup$ – user3184807 May 22 at 10:19

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.